214k views
4 votes
13÷[(-2)+3], (-31)÷[(-30)+(-1)] ,[(-6)+5]÷[(-2)+1]

User Bjarven
by
5.8k points

2 Answers

1 vote

Answer:

Use PEMDAS: Parentheses, Exponents, Mutliplication, Division, Addition, Subtraction.

13÷[(-2)+3] = 13

(-31)÷[(-30)+(-1)] = 1

[(-6)+5]÷[(-2)+1] = 1

*In this case, you solve for what's in the brackets.

Ex: 13÷[(-2)+3],

[(-2)+3] = -2 + 3 = 1. 13 divided by 1 = 13.

Hope this helps!!!

User Pavelgj
by
5.7k points
5 votes

Answer:

13

Explanation:

User Terite
by
5.2k points